Contrôle de la qualité microbiologique d’un poisson pélagique : Le maquereau espagnol Scomber japonicus (Houttuyn, 1782) pêché dans la région de Mostaganem - fall Alioune fall El mokhtar, Mokhtar (My University, 2024)
This study was carried out to assess the microbiological quality of Spanish mackerel (Scomber japonicus) in the Mostaganem region. The study focused on assessing the presence of bacteria indicative of faecal contamination, yeasts and moulds, and other pathogens in samples of mackerel taken from various covered market outlets in the centre of the town. The results revealed that the levels of microbiological contamination varied according to the germs detected from one contaminated sample to another. This was because the samples had a relatively low microbial load. However, the aim of the study was to monitor and assess the quality of the mackerel species, taking into account the microbiological limits set by the official journal. These results are important for guaranteeing the sanitary quality of mackerel, a widely consumed fish that is crucial to public health. Analysis of the samples revealed the presence of aerobic germs and streptocoques fécaux at satisfactory levels. However, total and faecal coliforms, levures and moisissures, Staphylococcus aureus, Clostridium sulfitoreductrices and salmonella were absent. These results were compared with the standards set by the Algerian official journal and it was established that the levels of micro-organisms detected did not exceed the microbiological reference limits. As a result, Spanish mackerel from Mostaganem can be considered safe for human consumption according to the microbiological quality criteria in force. The study also highlights the microbiological challenges associated with the distribution chain for Spanish mackerel in the Mostaganem region, and proposes solutions to guarantee better health quality for this seafood product. It also highlights the importance of maintaining rigorous hygiene practices throughout the distribution chain in order to minimise microbiological risks. Recommendations are made to improve the microbiological safety of mackerel, including stricter control measures.
Keywords: Scomber japonicus; Spanish mackerel; quality assessment of fish flesh; evaluation of the number of germs that deteriorate quality and cause toxicity in the product